Controlled growth of nanocrystalline aluminum nitride films for full color range. Issue 15 (1st August 2021) - Shi, Xunwang; Yu, Xiuhan; Nie, Caiwen; Li, Fengji; Zhang, Sam
Abstract: Color films are widely used for visual effect as well as for their functional properties. To date, however, synthesizing thin films with desired color remains challenging. In this work, AlN color films are deposited on Si wafers by precise control of the deposition time for different thickness during reactive magnetron sputtering from an Al target in Ar/N2 atmosphere. The thickness, morphology, structure, composition and color index are carefully examined by field emission scanning electron microscopy, atomic force microscopy, grazing incidence X-ray diffraction, X-ray photoelectron spectrometry and colorimeter, respectively. As the film thickness changes from 57 nm to 165 nm, the film exhibits purple, indigo, blue, green, yellow, orange and red in color. These colors repeat in the same order when the thickness goes over 165 nm. Once the thickness exceeds 467 nm, overlapping of colors takes place. The mechanisms are elucidated. Highlights: As film thickness is below 165 nm, interference effect results in purple, indigo, blue, green, yellow, orange and red. As film thickness is within 165-281 nm, same color reappears due to integer multiple change of optical path difference. Once film thickness exceeds 467 nm, color competition effect leads to the overlapping of multiple colors.